2021
DOI: 10.1002/mp.14665
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional MRI‐based treatment planning approach for non‐invasive ocular proton therapy

Abstract: Purpose To develop a high‐resolution three‐dimensional (3D) magnetic resonance imaging (MRI)‐based treatment planning approach for uveal melanomas (UM) in proton therapy. Materials/methods For eight patients with UM, a segmentation of the gross tumor volume (GTV) and organs‐at‐risk (OARs) was performed on T1‐ and T2‐weighted 7 Tesla MRI image data to reconstruct the patient MR‐eye. An extended contour was defined with a 2.5‐mm isotropic margin derived from the GTV. A broad beam algorithm, which we have called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…It is important to be aware that the limits of flat tumors are difficult to determine with both US and MRI. Moreover, the radiotherapy planning of UM with complex tumor shapes, such as some tumors with a mushroom configuration, is more difficult and deserves special attention [20]. The mushroom configuration is associated with breaks in Bruch's membrane [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to be aware that the limits of flat tumors are difficult to determine with both US and MRI. Moreover, the radiotherapy planning of UM with complex tumor shapes, such as some tumors with a mushroom configuration, is more difficult and deserves special attention [20]. The mushroom configuration is associated with breaks in Bruch's membrane [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…It is complicated to isolate the impact of dose parameters of eye structures that are in proximity, and it is therefore hard to determine whether the current planning strategy is suboptimal or not. Encouraging developments in the field of magnetic resonance imaging of the eye may enable more precise proton therapy planning in the near future [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should aim to further improve visual outcomes and reduce side effects. The integration of high-resolution imaging in proton therapy treatment planning will be a key step in this journey [ 45 ]. This and other studies showed that distant metastasis are common and impair overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Focalized radiotherapy techniques ensure a better control of dose delivery within the tumor, decreasing unnecessary irradiation of the surrounding healthy tissues and reducing radiation-induced vision loss. For this, better imaging systems, such as OCT technologies, choroidal doppler holography, and high-resolution magnetic resonance imaging (MRI), might increase the accuracy of the detection of tumor margins and ensure a precise delineation of the OAR [ 14 , 124 , 125 , 126 ]. Another way to retain visual function is preventive personalized treatment.…”
Section: Discussionmentioning
confidence: 99%